The Mediating Effects of Self-Acceptance and Self-Evaluation on Mindfulness and Benefit -Finding in a Sample of Chinese Systemic Lupus Erythematous Patients - Xu F; Tong X; Niu Y; Lin Q; Yao A; Yang F; Li L (Patient Preference and Adherence)
Fei Xu,1,* Xu Tong,2,* Yanping Niu,3 Qin Lin,3 Anling Yao,1 Feng Yang,4 Ling Li3 1School of Nursing, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 2School of Nursing, Bozhou College, Bozhou, Anhui, People’s Republic of China; 3School of Nursing, Zhejiang Shuren University, Hangzhou, Zhejiang, People’s Republic of China; 4Tongxiang First People’s Hospital, Tongxiang, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ling Li, School of Nursing, Zhejiang Shuren University, Hangzhou, People’s Republic of China, Email 59788937@qq.comPurpose: This study investigated the relationship between mindfulness, self-acceptance and benefit-finding in SLE patients. Through structural equation models, we examined the mediating role of self-acceptance and self-evaluation between mindfulness and benefit-finding.Patients and Methods: We used a convenient sampling method to investigate the demographics characteristics, mindfulness, self-acceptance, and benefit-finding of 319 SLE patients who were admitted to the rheumatology and immunology departments of tertiary, and Grade-A hospitals from December 2019 to December 2020.Results: Educational Levels, age, presence of other diseases besides SLE, medical expense payment method can affect mindfulness, and benefit-finding in SLE patients (p< 0.05), monthly salary can also influence mindfulness (p< 0.05), marital status also have impact on benefit-finding (p< 0.05). Educational Levels, age and monthly salary can affect the self-acceptance of SLE patients (p< 0.05). Mindfulness is positively correlated with the benefit-finding and has a significant positive impact on it (r=0.379, p< 0.01). Mindfulness is positively correlated with self-acceptance, and self-evaluation (r = 0.124 and 0.130, p < 0.05), which are positively correlated with the benefit-finding (r = 0.256 and 0.255, p < 0.05) in turn. Self-acceptance, and self-evaluation played a partially mediating role in the relationship between mindfulness, and the benefit-finding in SLE patients, with the mediating effect accounting for 7.95% (The path coefficient was 0.0391, p < 0.01), and 7.74% of the total effect (The path coefficient was 0.0384, p < 0.01), respectively.Conclusion: Mindfulness, self-acceptance, and benefit-finding in SLE patients are influenced by various sociodemographic factors. Self-acceptance and self-evaluation can mediate the relationship between mindfulness and benefit-finding in SLE patients. Clinical caregivers should pay more attention to improving patients’ levels of mindfulness and their self-acceptance of the disease, and guide patients in cognitive reappraisal, so that they can benefit from the struggle with the disease.Keywords: systemic lupus erythematosus, SLE, mindfulness, self-acceptance, benefit-finding, mediation role